The Hemiptera-Sternorrhyncha (Insecta) of Hong Kong, China—an annotated inventory citing voucher specimens and published records - Martin, Jon H.; Lau, Clive S.k. (Zootaxa, 2011)
An account of the Sternorrhyncha recorded from Hong Kong, comprising approximately 485 species, is presented. This is primarily based upon voucher holdings in the collection of the Natural History Museum, London and it includes incompletely identified taxa. Also included are records based solely on published data. Host plant data are included where known and there are four appendices for quick cross-reference of names, groups and hosts. One new species in the Aleyrodidae is described, Rhachisphora takahashii sp. nov.. One new synonymy in the Aleyrodidae is proposed, Aleurocanthus cheni Young (1942) becoming a junior synonym of A. spiniferus (Quaintance, 1903) syn. nov.. Two nomenclatural changes in the Psylloidea are proposed: Colophorina hungtouensis Fang & Yang (1986) comb. nov. is transferred from Psylla;  Macrohomotoma sinica Yang & Li (1984) is proposed as a junior synonym of M. gladiatum Kuwayama (1908), syn. nov.. One nomenclatural change in the Diaspididae (Coccoidea) is proposed: Neoparlatoria lithocarpi Takahashi (1934) is removed from synonymy with N. formosana Takahashi (1931), stat. rev.